Principal leadership orientations in vocational school transformation: A confirmatory factor analysis of regional public service agency transition in Indonesia - Puspitaningsih, Arin Ika; Burhanuddin, Burhanuddin; Imron, Ali; Sobri, Ahmad Yusuf (Journal of Interdisciplinary Studies in Education, 2026)
Indonesia’s transition of Vocational High Schools (VHS) to Regional Public Service Agency (RPSA) status demands strategic and adaptive principal leadership to optimize institutional performance and resource management. Yet persistent misalignment between administrative expectations and leadership practice undermines effective school transformation. This study examines the factor structure of principal leadership orientations during this transition using a quantitative design with Confirmatory Factor Analysis (CFA) applied to data from 316 purposively selected respondents in Indonesia. Three leadership orientation factors emerged: results focus, individual well-being, and team-oriented flexibility, with factor loadings ranging from 0.419 to 0.862, confirming construct validity.